Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.jtcvs.2013.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Modified surgical approach to symptomatic hypertrophic cardiomyopathy with abnormal papillary muscle morphology: Septal myectomy plus papillary muscle repositioning

Abstract: The Morrow procedure uses a midline sternotomy, with the left ventricle and septum accessed by the aortic valve through a vertical aortotomy. 4 The potential limitations of the procedure include small, but persistent, risks of an aortotomy (eg, postoperative bleeding, aortic dissection), difficulties with visualizing the surgical anatomy, and the risk of aortic valve damage (approximately 5% rate of moderate aortic regurgitation postoperatively 5 ).A robotic approach using the left atrium and across the mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…At the latest follow-up (14 months [IQR, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]), most of the patients were in acceptable physical state. Two male patients aged 15 and 14 years died of suspected sudden cardiac arrest 15 and 16 months after the operation, respectively.…”
Section: Middle-term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the latest follow-up (14 months [IQR, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]), most of the patients were in acceptable physical state. Two male patients aged 15 and 14 years died of suspected sudden cardiac arrest 15 and 16 months after the operation, respectively.…”
Section: Middle-term Resultsmentioning
confidence: 99%
“…12,13 Many procedures, including valve plication, papillary muscle repositioning, and secondary chordae cutting, have been reported to address mitral anomalies. [14][15][16] Gruner and colleagues 17 reported that left ventricular apical-basal muscle bundles were detected by cardiac magnetic resonance imaging in 63% of patients with HCM. In the present study, we report a large amount of data on detailed intraventricular anomalies that were directly observed by the operator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk of heart block can be minimized by beginning the septal resection at the nadir of the right aortic cusp and continuing it toward the left fibrous trigone. A hypertrophic anterior papillary muscle can supplement outflow tract obstruction, and muscular attachments to the septum must be divided (4). This should allow free motion of chordae tendineae and anterior mitral leaflet away from the septum during systole.…”
Section: Results and Pitfallsmentioning
confidence: 99%
“…Although there are many different surgical approaches and methods, the modi ed Morrow procedure through trans-aortic approach is still considered as the gold standard surgical treatment, showing a veri ed surgical result and good remission of symptoms for a long time [8,9,11]. The trans-mitral approach was rstly described in 1963 by Lillehei and Levy [10].…”
Section: Discussionmentioning
confidence: 99%